A Review of Corporate Social Responsibility: Its Perception, Practice, Impact and Challenges in Nigeria - Ezechukwu, Lynda Chineze; Uzuagu, Anthonia Uju (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2022)
Corporate social responsibility (CSR) has received comparatively less attention in developing countries like Nigeria. This review provides an overview of CSR in general including the conceptual definitions, aspects and benefits of CSR; and subsequently, focuses on the Nigerian context including the perception, practice, impact and contemporary challenges of CSR implementation in Nigeria. CSR, which has been defined in numerous ways, basically refers to the demand on business organisations to extend their relevance beyond profit making to taking responsibility for the welfare of their environment and stakeholders. Five aspects of CSR are discussed including economic, legal, ethical, philanthropic and political responsibilities. The perception and practice of CSR in Nigeria has been largely in the aspect of philanthropic responsibilities and although CSR activities of corporate organisations has been widely reported, the impact is yet apparently very low. Contributory to the reported low levels of CSR is the fact that the tone of CSR obligations of corporations in Nigeria is still largely voluntary, unlike in some countries like India and China that have made CSR mandatory by law. Recent empirical studies reviewed on the outcomes of CSR in Nigeria showed both positive and negative outcomes of CSR on businesses, suggesting that more research is needed to validate the findings. Finally, challenges to CSR implementation in Nigeria include: failure of government, lack of an effective CSR enforcement framework, institutionalized corruption as well as political and social insecurity.